First cut : a season in the human anatomy lab - Carter, Albert Howard, 1943- (New York : Picador USA, 1998)
The author provides an account of the semester he spent observing first-year medical students dissect cadavers at Emory University in Atlanta, and teaches lessons about the human body and the process of becoming a doctor.
Kirkus Review.
Publisher's Weekly.
Adult
Keywords: Emory University. -- School of Medicine; Emory University. -- School of Medicine; Human anatomy -- Study and teaching (Graduate) -- Georgia -- Atlanta; Human dissection -- Georgia -- Atlanta; Human anatomy -- Study and teaching